Life of a single cell : a programmer's approach - Wong, Beckham Chin Kiat (Nanyang Technological University, 2020)
The focus of this paper is the modelling and simulation of three main mechanics of the free swimming planktonic Escherichia coli, or E. coli cell. These three mechanics are the random walk, chemotaxis and secretion or cell-cell communication. The base model used to simulate all the mechanics is the one developed by Berg & Brown, which is based on the rate of change of bound chemical receptors (Berg & Brown, Chemotaxis in Escherichia coli analysed by Three Dimensional Tracking, 1972). Additionally, simulations of two experimental setups were also performed. The results of the simulations were then compared to the results of the actual experiments. It was found that the simulations of pure chemotaxis without secretion resulted in the replication of key observations in actual experiments. The cells showed strong response to the chemical, and also had a peak response at a particular intermediate concentration of the chemical. Differences from experimental results were also seen. The primary difference involved the significantly lower response at high concentrations in the simulations when compared to actual experiments. This was explained to be caused by the reliance on α, an empirical constant, which required a different value at the higher concentration range. Additionally, simulations results of the constant, independent secretion model showed insignificant increases in response when compared to a pure chemotaxis without secretion. With the constant independent secretion model, the response of the cells was overwhelmingly dominated by the nutrient chemical and the response to the self-secreted chemical was minimal. This was shown to be the case for various concentrations of secretion, as well as various values of dissociation constant. It was thus concluded that the secretion mechanic of actual cells could instead involve other methods, such as secreting chemicals only when increasing chemical concentration is detected.